Properties of calcium aluminate blended cement incorporating iron-rich slag: Evolution over a curing period of 1 year. (3rd May 2021) - Astoveza, Jennifer; Trauchessec, Romain; Soth, Ratana; Pontikes, Yiannis
Highlights: Evidence of long term (> 28 days) slag reactivity based on the evolution of properties. Dimensional stability is demonstrated through shrinkage test over 1 year curing period. The hydrate phase assemblage rich in monosulfoaluminate is modified by the slag dissolution. Using XCT, the slag hydration degree was calculated to be 49% after 1 year of curing. The overall properties support the potential valorization of the slag as SCM in the CAC-based blend. Abstract: With an outlook directed towards circular economy, the valorization of municipal waste streams and industrial residues has recently conveyed a variety of novel industrial by-products to various applications such as supplementary cementitious materials (SCM) in cement blends or as precursors to inorganic polymers. Despite the synergistic benefits on recycling, reducing the cost and the carbon footprint of cements, the use of such non-conventional SCM is often limited to ordinary Portland cement (OPC)-based formulations. This study investigates the properties of a calcium aluminate cement (CAC)-based blend incorporating 30 wt% of iron (Fe)-rich slag produced at pilot scale from an industrial lead–zinc production. Compressive and flexural strength (EN 196-1 standard mortars), setting time, dimensional stability (Walter + Bai shrinkage measuring test), early hydration reactions (isothermal calorimetry), and phase assemblage evolution (XRD and TGA) were followed from 1 day to 1 year of curing period for both the slag-containing- and a corresponding reference cement formulation. Additionally, a fast non-destructive technique for quantifying the degree of slag hydration is demonstrated using a combination of X-ray computed tomography (XCT) and volume analysis based on grayscale threshold segmentation. The results from the different techniques suggest the long term (>28 days) reactivity of the slag with the slag-containing mortars attaining a comparable compressive strength of 39 MPa versus 41 MPa of the corresponding reference mortars at 90 days. Likewise, the prominent contribution of the slag to the hydration reactions is manifested by the differences in the evolution of the phase assemblage of the two formulations. The degree of slag hydration was calculated to progressively increase over time reaching up to 49% after 1 year of hydration based on the XCT scans. These results along with the long term dimensional stability of the slag-containing formulation support the potential for valorization of the Fe-rich slag as SCM in the CAC-based blend.